Charge-lattice coupling and the dynamic structure of the U–O distribution in UO2+x - Lewis, Jarrod; Springell, Ross; Bell, Christopher; Nicholls, Rebecca; Wasik, Jacek; Harding, Lottie; Gupta, Mahima; Pakarinen, Janne; Baldinozzi, Gianguido; Andersson, David; Guo, Xiaofeng; Conradson, Steven D. (Frontiers in Nuclear Engineering, 2024)
The different structures and behaviors of UO 2+x observed in crystallographic and local structure measurements are examined by Extended X-ray Absorbance Fine Structure (EXAFS) measurements of pristine UO 2.0 , p + and He 2+ irradiated UO 2.0 , and at multiple temperatures bulk U 4 O 9 and U 3 O 7 and thin film U 4 O 9-δ on an epitaxial substrate. The disorder caused by irradiation is mostly limited to to increased widths of the existing U-O/U pair distributions with any new neighbor shells being minor. As has been previously reported, the disorder caused by oxidative addition to U 4 O 9 and U 3 O 7 is much more extensive, resulting in multisite U-O distributions and greater reduction of the U-U amplitude with different distributions in bulk and thin film U 4 O 9 . This includes the significant spectral feature near R=1.2 Å for all of the U 4 O 9 and U 3 O 7 samples that is fit with a U-oxo type moiety with a U-O distance around 1.7 Å. In addition to indicating that these anomalies only occur in the mixed valence materials, this work confirms the continuous rearrangement of the U-O distributions from 10-250 K. Although these variations of the structure are not observed in crystallography, their prominence in the EXAFS indicates that the dynamic structure underlying these effects is an essential factor of these materials.